Informality and macroeconomic volatility : do credit constraints matter? (2015)
ABSTARCT: Hiding operations from tax collectors increases information asymmetries between borrowers and lenders and ultimately reduces firms' access to finance. However, credit-constrained entrepreneurs can still fund investment by paying it out of their own savings. This paper studies these implications of borrowing constraints characterizing the informal sector for macroeconomic volatility. To this end, the author develops a simple dynamic stochastic general equilibrium model featuring tax avoidance and evasion opportunities. In the model, registered production not only is the basis to determine tax liabilities, but also serves as collateral for securing debts. Such a framework allows for endogenization of the extent of undeclared activity, and for analyzing the effect of informality on aggregate fluctuations through computational experiments. These experiments show that the borrowing-constrained informal sector exerts a non-negligible influence on the cyclical volatility of consumption and investment. Some qualifications and extensions conclude this work.